Indium and zinc mediated Barbier type reactions: Allylation and propargylation reactions of 6-oxopenicillanate and 7-oxocephalosporanate - Cho, YS; Lee, JE; Pae, AN; Choi, KI; Koh, HY (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
Allylation and propargylation of compounds, 6-oxopenicillanate 1 and 7-oxocephalosporanate 2, were accomplished by reacting the corresponding bromides in the presence of indium or zinc. Both indium and zinc gave alkylated products in moderate yields under mild conditions. Indium mediated Barbier reactions in aqueous THF exhibited slightly higher stereoselectivity than zinc mediated reactions in anhydrous THE (C) 1999 Elsevier Science Ltd. All rights reserved.